On the Relevance and Limitations of Predictive Models in Clinical Psychology - Emanuele Maria Merlo (Mediterranean Journal of Clinical Psychology)
Following a relevant contribution promoted by the American Psychological Association (Hanson, 2022), prediction statistics in Clinical Psychology represent a series of practices useful to predict the effect of an independent variable on possible outcomes.